Relaciones entre la tendencia y el ciclo económico - Rosato, María Luisa (1962)
In order to determine whether there is a relation between trend and Business cycle we have first to review the studies published by authors who wrote on this subject: H. Guitton, N. Kaldor, N. Fanno, G. Demaría, J. Schumpeter, A. Marchal, G. Akerman, etc. Considering that the countries are endeavouring to achieve the expansion of their economies, avoiding at the same the impact of strong periodic oscillations, it would be convenient to investigate the connections between the fluctuations and economic expansion. Although the investigations are generally referred to capitalistic, highly industrialized countries and Argentina still has as economic structure fundamentally based on agriculture and cattle breeding, it is nevertheless interesting to know the problems which affect the manufacturing economies and the solutions given to them. The author admits the connection between trend and economic fluctuation and prefers the long-run analysis.